A New Model to Evaluate Activity Coefficients of Strong Electrolytes in Aqueous Solutions. - ABDEL-HALIM, H.M. (Asian Journal of Chemistry, 2010)
A simple model to calculate the mean activity coefficient based on the Debye-Hückel model is introduced. An empirical formula is given for the calculation of the distance of closest approach for simple salts in aqueous medium. The mean activity coefficients for several salts are calculated in the range 0.001–7.0 m. Good agreement with experimental values is observed.